Persistently Elevated Microvascular Resistance Postrecanalization: A Clinical Marker of No-Reflow Phenomenon. Issue 10 (October 2018) - Ng, Felix C.; Coulton, Bronwyn; Chambers, Brian; Thijs, Vincent
Abstract : Background and Purpose—: Impaired microvascular reperfusion despite complete recanalization (no-reflow) represents a potential therapeutic target to improve outcomes after recanalization therapies. Although well documented in animal models, this phenomenon has not been demonstrated clinically. We investigated whether transcranial Doppler can detect acute microvascular changes postrecanalization as a biomarker of the no-reflow phenomenon in stroke patients. Methods—: Consecutive patients with recanalized (Thrombolysis in Cerebral Infarction grade IIb/III) acute middle cerebral artery occlusion by thrombectomy at a Comprehensive Stroke Centre with a high-volume neurovascular laboratory were retrospectively identified. Sonographic measures of middle cerebral artery territory microvascular resistance (pulsatility index and resistive index) on days 1 to 3 follow-up transcranial Doppler were compared between patients and age/gender-matched controls. Results—: In 53 patients, middle cerebral artery pulsatility index was significantly more likely to be asymmetrically increased on interside comparison (27.9% versus 4.9%; P =0.007) and abnormally elevated beyond normal reference ranges (46.7% versus 22.0%; P =0.016) in the symptomatic hemisphere. Middle cerebral artery pulsatility index elevation was associated with less hemorrhagic infarction (9.5% versus 45.8%; P =0.009) but worse functional outcome irrespective of infarct volume as assessed on 90-day modified Rankin Scale (score of ⩽1, 18.2% versus 58.1%; P =0.035). Conclusions—: Elevated microvascular resistance within the ischemic territory is commonly present after successful recanalization as measured by pulsatility index on transcranial Doppler and may be a readily available and clinically relevant biomarker of the no-reflow phenomenon. Abstract : Supplemental Digital Content is available in the text.